2003
DOI: 10.1128/aem.69.10.5968-5973.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Chemotaxis to Naphthalene Desorbing from a Nonaqueous Liquid

Abstract: Bacterial chemotaxis has the potential to increase the rate of degradation of chemoattractants, but its influence on degradation of hydrophobic attractants initially dissolved in a non-aqueous-phase liquid (NAPL) has not been examined. We studied the effect of chemotaxis by Pseudomonas putida G7 on naphthalene mass transfer and degradation in a system in which the naphthalene was dissolved in a model NAPL. Chemotaxis by wild-type P. putida G7 increased the rates of naphthalene desorption and degradation relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 38 publications
1
71
1
Order By: Relevance
“…Chemotaxis, the ability of motile bacteria to detect and respond to specific chemicals, can help bacteria find an optimal niche for their survival and growth and may play a role in the efficient degradation of pollutants in the environment (33,37). Chemotaxis has been shown to enhance naphthalene biodegradation in both a heterogeneous aqueous system (30) and a non-aqueous-phase liquid system (24). In addition, a chemotactic naphthalene-degrading strain caused a higher rate of naphthalene desorption than was observed with nonchemotactic and nonmotile strains (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotaxis, the ability of motile bacteria to detect and respond to specific chemicals, can help bacteria find an optimal niche for their survival and growth and may play a role in the efficient degradation of pollutants in the environment (33,37). Chemotaxis has been shown to enhance naphthalene biodegradation in both a heterogeneous aqueous system (30) and a non-aqueous-phase liquid system (24). In addition, a chemotactic naphthalene-degrading strain caused a higher rate of naphthalene desorption than was observed with nonchemotactic and nonmotile strains (24).…”
mentioning
confidence: 99%
“…Chemotaxis has been shown to enhance naphthalene biodegradation in both a heterogeneous aqueous system (30) and a non-aqueous-phase liquid system (24). In addition, a chemotactic naphthalene-degrading strain caused a higher rate of naphthalene desorption than was observed with nonchemotactic and nonmotile strains (24). Pseudomonas sp.…”
mentioning
confidence: 99%
“…Suspensions of wild-type, nonmotile, and nonchemotactic (51) Pseudomonas putida G7 were prepared as described previously (45). Briefly, batches of bacterial cultures were grown by lightly scraping a frozen stock (Ϫ70°C) with a sterile wooden applicator stick and transferring the scraping to tryptone broth.…”
Section: Methodsmentioning
confidence: 99%
“…16 The best studied example of chemotaxis-enhanced bioavailability (and 17 biodegradation) of a PAH relates to the capacity of Pseudomonas putida G7 to degrade 18 naphthalene, and several studies have focused on this strain as a model microorganism. 19 Using a heterogeneous aqueous system under a slow-diffusion regime, the rate of that also used chemotactic and non-chemotactic strains of P. putida G7 clearly 25 demonstrated that chemotaxis increased naphthalene degradation when the compound is 1 present in a non-aqueous-phase liquid (NAPL) [117]. In this case, chemotaxis promoted 2 partitioning and biodegradation of naphthalene by creating a steeper gradient as the cells 3 accumulated near the NAPL/water interface.…”
mentioning
confidence: 99%